Фауна блох (Suctoria) гнезд мыши курганчиковой (Mus sergii Valch) Юго-Западной Украины - Волянский, Ю.Е. (Вестник зоологии, 1969)
Thirty nests of Mus sergii Valch were found from September till May in 1964— 1966 near Odessa. Suctoria of the following 5 species were detected in them: Ctenophthal-mus (Euctenophthalmus) orientalis W a g n., Ceratophyllus (Nosopsyllus) mokrzeckyi Wagn., C. (Nosopsyllus) Consimilis Wagn., Rhadinopsylla (Rhadinopsylla s. str.) ukrainica I о f f, Stenoponia tripectinata T і r a b. The most numerous species proved to be Ct. orientalis (52%), C. mokrzeckyi (25%) and St. tripectinata (19%), R. ukrainica and C. Consimilis were found as single specimens.